2011
DOI: 10.1007/s11104-011-0935-3
|View full text |Cite
|
Sign up to set email alerts
|

Root-induced processes controlling phosphate availability in soils with contrasted P-fertilized treatments

Abstract: In this study we identified the nature of the root-induced chemical processes controlling changes in phosphate (P) availability in a soil with two P loadings resulting from long-term fertilization treatments. We used a set of mechanistic adsorption models (surface complexation and ion exchange) within the framework of the component additive approach to simulate the effect of durum wheat roots on P availability. We had to consider the influence of adsorption of other ions to ensure the goodness-of-fit of the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 62 publications
1
17
2
Order By: Relevance
“…Such alkalization in the rhizosphere of maize (see Fig. 7d) agrees with previous studies on other cereals intercropped with legumes Devau et al 2011b;Betencourt et al 2012). For maize intercropped with legumes, this would lead to rhizosphere alkalization if Ca were not taken up by maize.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Such alkalization in the rhizosphere of maize (see Fig. 7d) agrees with previous studies on other cereals intercropped with legumes Devau et al 2011b;Betencourt et al 2012). For maize intercropped with legumes, this would lead to rhizosphere alkalization if Ca were not taken up by maize.…”
Section: Discussionsupporting
confidence: 91%
“…Most studies reported depletion of P availability in the rhizosphere via plant root uptake during the crop cycle (Hinsinger 2001;Hinsinger et al 2011;Pan et al 2008). Only a few recent studies have shown an increase in P availability in the rhizosphere of durum wheat and chickpea (Devau et al 2010(Devau et al , 2011bBetencourt et al 2012). However, these studies were conducted under controlled conditions using rhizobox and pot experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, plant P concentrations increased linearly with fertilizer rates. Some plants can modify the soil chemical properties such as pH and the cation exchange capacity by exuding organic acids in the rhizosphere (Devau et al, 2011). However, in the present experiment the average pH was 5.2 in RH and 5.4 in TH and it was not affected by phosphate fertilization or Congo grass (results not shown).…”
Section: Resultscontrasting
confidence: 70%
“…The effect of cover crops, mainly legumes, enhancing P availability has been observed before (Kamh et al, 1999;Richadson et al 2011;Hassan et al, 2013), but results on the effect of no-till on available P are inconclusive and depend on the soil type (Zibilske et al, 2002;Pavinato et al, 2009;Devau et al, 2011). However, these results were obtained in a pot experiment where roots were very close together and the proportion of rhizosphere soil is higher than it would be under field conditions.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation